Analysis of the Management of School Operational Assistance Funds at the Palu Potential Vocational High School - Rajindra Rajindra; Mardiah Mardiah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
The results of the management analysis show that the School Operational Assistance funds received by SMK Bina Potential Palu in 2016 amounted to Rp. 278,250,000, while the realization of the use of BOS funds was Rp. 278,250,000, this implies that the use of BOS funds at SMK Bina Potential Palu has been realized optimally and effectively. However, based on research, shows that there are several components whose use is outside the budget plan prepared by the school. So there are some components that experience minus their use. According to information obtained from SMK Bina Potential Palu, the delay in distributing BOS funds became an obstacle in meeting school operational needs, so schools had to use funds collected from student tuition fees.